Effects of apocynin, an NADPH oxidase inhibitor, on levels of ADMA, MPO, iNOS and TLR4 induced by myocardial ischemia reperfusion - Uysal, A.; Sahna, E.; Ozguler, I. M.; Burma, O.; Ilhan, N. (Sage Publications Ltd, 2015)
Purpose: In this study, the effects of apocynin, an NADPH oxidase inhibitor, on the levels of inducible nitric oxide synthase (iNOS) and the toll-like receptor 4 (TLR4), which are inflammatory mediators in myocardial ischemia-reperfusion (MIR) injury, and myeloperoxidase (MPO), which is the indicator of neutrophil infiltration and the endogenous nitric oxide synthase inhibitor asymmetric dimethyl arginine (ADMA) increasing with oxidative stress were investigated. Methods: MIR injury was accomplished by the application of occlusion for 30 minutes and reperfusion for 120 minutes in the left anterior descending artery (LAD). In the study, 21 Sprague-Dawley male rats were divided into three groups: a sham group (n = 7); a MIR group (n = 7); and a MIR + apocynin treatment group (n = 7, before the procedure, an intraperitoneal administration of 10 mg/kg of apocynin for 15 days). After reperfusion, iNOS, TLR4, MPO and ADMA levels in myocardial tissue were measured by ELISA. Results: While myocardial TLR4, MPO and ADMA levels increased in the MIR group, these parameters were found to be decreased significantly in the group treated with apocynin. Although iNOS levels showed an increase in the MIR group compared to the sham group and a reduction in the MIR+apocynin group, there was no statistically significant difference between the groups. Discussion: In our study, the effect of the treatment of apocynin in MIR on ADMA, MPO, iNOS and TLR4 levels in myocardial tissue was shown for the first time. It is thought that apocynin treatment may show a protective effect in MIR injury by affecting oxidative stress (ADMA) and inflammatory parameters (iNOS, MPO).
Keywords: apocynin; myocard; ischemia; TLR-4; ADMA